1994
DOI: 10.1080/01652176.1994.9694423
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of preantral follicles from foetal bovine ovaries

Abstract: A simple, mechanical method is described for the isolation of preantral follicles from bovine foetuses of 220-280 days of gestation. On average, 2918 + 621 (s.d.) preantral follicles were isolated per ovary. The isolated preantral follicles were characterized on the basis of the morphological appearance of the surrounding granulosa cells, the number of granulosa cell layers, and their diameter. The results show that primordial, primary, and secondary follicles differ morphologically and that they can be classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 11 publications
(14 reference statements)
2
57
1
1
Order By: Relevance
“…Other studies showed similar results in the isolation of preantral follicles using a tissue chopper [2,4,34]. In contrast, Hulshof et al [15], using watch maker's forceps to isolate preantral follicles, observed a lower percentage of isolated primordial follicles (12.5%) when compared to primary (57.2%) and secondary (20.7%) follicles. These authors suggest that it may be due to primordial follicles being tightly embedded in the tunica albuginea [15], and a mild mechanical treatment is not sufficient to isolate these follicles.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Other studies showed similar results in the isolation of preantral follicles using a tissue chopper [2,4,34]. In contrast, Hulshof et al [15], using watch maker's forceps to isolate preantral follicles, observed a lower percentage of isolated primordial follicles (12.5%) when compared to primary (57.2%) and secondary (20.7%) follicles. These authors suggest that it may be due to primordial follicles being tightly embedded in the tunica albuginea [15], and a mild mechanical treatment is not sufficient to isolate these follicles.…”
Section: Discussionmentioning
confidence: 78%
“…Other researchers isolated a large number of ovarian preantral follicles from European cows [3,15,24], goats [4,6], ewes [2,5], pigs [25], domestic cats [26,27] and nondomestic felids [28,29], rabbits [30], rats [31], mice [32], and humans [33], using mechanical [2^1, 15,24,[26][27][28][29] or enzymatic [25,[30][31][32][33] procedures. Comparisons between our results and those of other studies are difficult to perform due to species differences, variation in follicle classification, and types of follicles included in the final count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small fragment of each ovarian piece was removed for electron microscopy. The remainder was fixed in Carnoy fixative for 4 h, [7]. Follicle quality was concurrently evaluated.…”
Section: Histological Analysismentioning
confidence: 99%
“…Sections of 7 μm were stained with periodic acid Schiff (PAS) and haematoxylin. Preantral follicles were classified by their morphological appearance, according to Hulshof et al (1994). The diameters of the follicles and the oocytes were determined when the nucleolus of the oocyte was observed (equatorial section), using an ocular micrometer and considering the smaller diameters.…”
Section: Light Microscopymentioning
confidence: 99%